Peningkatan Pengetahuan Masyarakat dalam Penerapan Protokol Kesehatan melalui Edukasi Berbasis Media Online - I Putu Sudayasa; Haryati Haryati; Yenti Purnamasari; Yulin Fitri Chintia; Nur Riska Anwar; Putri Permatasari; Pebriyanti Pebriyanti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The Indonesian government has made various efforts to prevent and control COVID-19. Implementing the new normal after the COVID-19 pandemic has encouraged people to do activities as before, with the obligation to implement strict health protocols. However, the incidence of COVID-19 in Indonesia continues to increase, as is Konawe Regency as the district with the first positive case report of COVID-19 in Southeast Sulawesi and currently has six sub-districts with red zone status. This is because many people are not aware of carrying out the government's appeal in implementing health protocols. This community service aims to increase public knowledge in efforts to control COVID-19 by applying health protocols. Educational activities carried out online through online media include video conferencing in the form of a webinar through Google Meet was attended by 86 participants, live streaming on social media Facebook and Instagram, broadcasting educational videos on local TV channels, and conducting offline activities in the form of installing educational posters. Education through online media is one of the uses of internet technology, and its reach is wide and can be a solution for education during the COVID-19 pandemic. The analysis results show that education through online media effectively increases public knowledge regarding COVID-19 and the application of health protocols in the normal new era.